Bactericidal and Virucidal Activities of Biogenic Metal-Based Nanoparticles: Advances and Perspectives - Gonzalo Tortella; Olga Rubilar; Paola Fincheira; Joana C. Pieretti; Paola Duran; Isabella M. Lourenço; Amedea B. Seabra (MDPI AG, 2021)
Much progress has been achieved in the preparation and application of engineered nanoparticles (NPs) in the field of medicine, mainly for antibacterial and antiviral applications. In the war against bacteria and viruses, besides traditional antibiotics and antiviral drugs, metal-based nanoparticles, such as silver (AgNPs), copper (CuNPs), copper oxides (CuO-NPs), iron oxide (FeO-NPs), zinc oxide (ZnO-NPs), and titanium oxide (TiO2-NPs) have been used as potent antimicrobial agents. These nanoparticles can be synthesized by traditional methods, such as chemical and physical routes, or more recently by biogenic processes. A great variety of macro and microorganisms can be successfully used as reducing agents of metal salt precursors in the biogenic synthesis of metal-based NPs for antimicrobial activity. Depending on the nature of the biological agent, NPs with different sizes, aggregation states, morphology, surface coatings and charges can be obtained, leading to different antimicrobial effects. Considering the drug resistance to traditional therapies, the development of versatile nanomaterials with potent antimicrobial effects is under intensive investigation. In this sense, this review presents and discusses the recent progress in the preparation and application of metal-based nanoparticles biogenically synthesized for antibacterial and antivirus applications. The strength and limitations are critically discussed.